Advancements in Artificial Intelligence for Health: A Rapid Review of Ai-Based Mental Health Technologies Used in the Age of Large Language Models - Rojas-Andrade, R; Cabrera-Medina, J (Springer Science and Business Media Deutschland GmbH, 2024)
This paper aims to explore the advancements of AI technologies in mental health by conducting a rapid review of recent scientific literature and mass media outputs. The study focuses on identifying AI technologies used in mental health, outlining the types of interventions benefiting from these technologies, evaluating the scientific evidence on their safety and effectiveness, and assessing the existence of normative frameworks that ensure their ethical use. Employing a rapid review methodology, this research scrutinizes scientific studies and media reports selected based on explicit relevance to AI and mental health. The review integrates both scientific and grey evidence, providing a comprehensive overview of the current state and potential of AI applications in mental health care. The findings reveal significant utilization of AI in mental health diagnostics, treatment planning, and therapeutic interventions, facilitated by tools such as natural language processing, machine learning algorithms, and integrated AI systems, such as robots. The study also highlights the ethical, safety, and regulatory challenges emerging from the massive use of AI in this field, reflecting the need for stringent oversight and continuous evaluation. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.